Role of the Vision Van, a mobile ophthalmic outpatient clinic, in the Great East Japan Earthquake - Yuki K (Dove Medical Press, 2014)
Kenya Yuki,1 Toru Nakazawa,2 Daijiro Kurosaka,3 Tsunehiko Yoshida,4–6 Eduardo C Alfonso,7 Richard K Lee,7 Shigeru Takano,8 Kazuo Tsubota1 1Department of Ophthalmology, Keio University School of Medicine, Tokyo, Japan; 2Department of Ophthalmology, Tohoku University Graduate School of Medicine, Miyagi, Japan; 3Department of Ophthalmology, Iwate Medical University, Iwate, Japan; 4The House of Representatives of Japan, Tokyo, Japan; 5Nagoya University Hospital, Aichi, Japan; 6Aichi Medical University Hospital, Aichi, Japan; 7Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USA; 8Japan Ophthalmological Association, Tokyo, Japan Purpose: The Great East Japan Earthquake of March 11, 2011 triggered powerful tsunami waves off the northeastern Pacific coast of Japan that destroyed almost all of the built-up areas along the coast. The study reported here examined the role played by the Vision Van, a mobile outpatient ophthalmological clinic, in providing eye care to disaster evacuees. Methods: This was a retrospective case-series study of 2,070 victims (male: 732, female: 1,338) who visited the Vision Van. The subjects' medical records were examined retrospectively and analyzed in terms of age, sex, and date of visit to the Vision Van. Information regarding each patient's chief complaint, diagnosis, medication(s) prescribed, and eyeglasses and contact lenses provided, was also examined. Results: The Vision Van was used to conduct medical examinations on 39 days between April 23 and June 29, 2011. The average number of subjects visiting the Vision Van each day was 53±31 (range: 7–135), with examinations carried out in Miyagi Prefecture and Iwate Prefecture. The most frequent complaint was a need for eye drops (871/2,070 [42.1%]). The second and third most frequent complaints, respectively, were the need for contact lenses (294/2,070 [14.2%]) and eyeglasses (280/2,070 [13.5%]). The most frequent ocular disease diagnosis was cataract (497/2,070 [24.0%]). Eye drops were prescribed to 74.1% of the subjects. Conclusion: Mobile clinics such as the Vision Van provide valuable care, in this case, particularly to individuals who lost or left behind eyeglasses or contact lenses while escaping a natural disaster, and to subjects with chronic eye disease. Keywords: natural disaster, disaster relief, eye care, mobile medical services